2018
DOI: 10.1002/mgg3.411
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐exome sequencing for variant discovery in blepharospasm

Abstract: BackgroundBlepharospasm (BSP) is a type of focal dystonia characterized by involuntary orbicularis oculi spasms that are usually bilateral, synchronous, and symmetrical. Despite strong evidence for genetic contributions to BSP, progress in the field has been constrained by small cohorts, incomplete penetrance, and late age of onset. Although several genetic etiologies for dystonia have been identified through whole‐exome sequencing (WES), none of these are characteristically associated with BSP as a singular o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 98 publications
0
16
0
2
Order By: Relevance
“…Deleterious mutations in HS1BP3 encoding hematopoietic cell-specific Lyn substrate 1-binding protein 3 (NM_022460.3: c.94C>A, p.Gly32Cys) and GNA14 encoding G protein subunit α14 (NM_004297.3: c.989_990del, p.Thr330ArgfsTer67) were present in a father and son with segmental CCD that initially presented as BSP. Additionally, deleterious variants of genes encoding dynein axonemal heavy chain ( DNAH17 ); transient receptor potential cation channel subfamily V member 4 ( TRPV4 ); calpain 11 ( CAPN11 ); vacuolar protein sorting 13 homolog C ( VPS13C ); unc-13 homolog B ( UNC13B ); spectrin β, non-erythrocytic 4 ( SPTBN4 ); myogenic differentiation 1 ( MYOD1 ); and mitochondrial ribosomal protein L15 ( MRPL15 ) have been found in two or more unrelated BSP patients ( 78 ). Despite the identification of many gene mutations in BSP, OMD, and MS patients, the mutation rates of these genes are low and it is a lack of functional experiments of mutant genes.…”
Section: Geneticsmentioning
confidence: 99%
“…Deleterious mutations in HS1BP3 encoding hematopoietic cell-specific Lyn substrate 1-binding protein 3 (NM_022460.3: c.94C>A, p.Gly32Cys) and GNA14 encoding G protein subunit α14 (NM_004297.3: c.989_990del, p.Thr330ArgfsTer67) were present in a father and son with segmental CCD that initially presented as BSP. Additionally, deleterious variants of genes encoding dynein axonemal heavy chain ( DNAH17 ); transient receptor potential cation channel subfamily V member 4 ( TRPV4 ); calpain 11 ( CAPN11 ); vacuolar protein sorting 13 homolog C ( VPS13C ); unc-13 homolog B ( UNC13B ); spectrin β, non-erythrocytic 4 ( SPTBN4 ); myogenic differentiation 1 ( MYOD1 ); and mitochondrial ribosomal protein L15 ( MRPL15 ) have been found in two or more unrelated BSP patients ( 78 ). Despite the identification of many gene mutations in BSP, OMD, and MS patients, the mutation rates of these genes are low and it is a lack of functional experiments of mutant genes.…”
Section: Geneticsmentioning
confidence: 99%
“…Therefore, in this study we examined 151 genes in all BEB patients and found SYNE1 gene mutation in seven cases, CIZ1 gene mutation in two cases, CACNA1A gene mutation in two cases, LRRK2 gene mutation in two cases, FUS gene mutation in two cases, and C10orf2, TPP1, SLC1A3, PNKD, EIF4G1, SETX, PRRT2, SPTBN2, and TTBK2 gene mutation in each case. Interestingly, a recent study showed that deleterious variants in CACNA1A, REEP4, TOR2A, ATP2A3, HS1BP3, GNA14, and DNAH17 were involved in blepharospasm, and none of these variants except for CACNA1A has been reported to be associated with blepharospasm (15). However, a follow-up study reported that all variants detected in GNAL, CIZ1, and TOR2A seemed to be benign in 132 blepharospasm patients (16).…”
Section: Discussionmentioning
confidence: 99%
“…The second stage of genetic analysis was performed with whole exome sequencing (WES) of three subjects (II/2, III/1, and III/2) using Illumina HiSeq 2500 platform (Illumina, San Diego, CA, USA). Genomic DNA was sheared to yield 100–450 base pair (bp) fragments, which was described before [ 16 ]. In-solution whole-exome capture and massively parallel sequencing was performed using the Agilent SureSelect XT All Exon Kit 51 Mb (Agilent, Santa Clara, CA, USA).…”
Section: Methodsmentioning
confidence: 99%